(untitled) (Pedagogical Horizons, 2021)
Children explore their world and perceive it with all their senses. Pedagogical Professionals have the task of accompanying children in their individual and unique educational and learning processes and to provide them with diverse impulses. The observation and documentation of children’s activities is seen as an important basis for planning and designing educational offers based on the individuality of each child. The children’s world is shaped by socio-cultural structures, such as the gender ratio, and children try to find their place in it. They bring their gender-related ideas into everyday life in preschool institutions. They actively participate in the creation of gender. This article takes up the multi-layered and complex processes of observation and documentation and draws attention to gender-conscious access to preschool education.